Framework for agricultural cooperatives: a study on governance structure, conductand performance - da Costa Sccott, Carla Rosane; B. Brandão, Janaína; Breitenbach, Raquel; Reisdorfer, Vitor K. (Cooperativismo & Desarrollo, 2024)
The aim of this study was to propose a governance and conduct structure framework to contribute to the performance of cooperatives. The methodology is descriptive and quantitative research, with questionnaires applied to 20 agricultural cooperatives in Rio Grande do Sul and 20 in Paraná. It also includes exploratory research approaching a qualitative data analysis and interpretation using the Qualitative Comparative (QCA) method. The results showed that the governance structures most associated with superior financial performance are the least hierarchical structures combined with more cooperative conduct. The conclusion about financial performance says that 69.44% of the cooperatives studied (RS and PR) presented intermediate and superior economic performance, with a predominance of more cooperative conduct. Also, this allows us to see that the choice of the form of governance and conduct structure is sustaining a competitive advantage concerning its competitors in the challenge of not losing its cooperative identity. Regarding social performance, despite the alignment mentioned in the results found, it is not possible to say with certainty that cooperative behaviors are associated with better social performance.